A three-year longitudinal evaluation of the forearm bone density of users of etonogestrel- and levonorgestrel-releasing contraceptive implants - Monteiro Ilza; Fernandes Arlete M; Lui-Filho Jeffrey F; Espejo-Arce Ximena; Monteiro-Dantas Cecilia; Bahamondes Luis (BMC, 2007)
Abstract Background The aim of this study was to evaluate bone mineral density (BMD) at baseline and at 18 and 36 months of use of etonogestrel (ENG)-and levonorgestrel (LNG)-releasing contraceptive implants. This is a continuation of a previous study in which BMD was evaluated at baseline and at 18 months of use. Methods A total of 111 women, 19-43 years of age, wererandomly allocated to use one of the two implants. At 36 months of follow-up, only 36 and 39 women were still using the ENG- and LNG-releasing implants, respectively. BMD was evaluated at the distal and at the ultra-distal radius of the non-dominant forearm using dual-energy X-ray absorptiometry. Results There was no difference in the BMD of users of either implant at 18 and at 36 months. BMD was significantly lower at 18 and at 36 months at the distal radius in both groups of users compared to pre-insertion values; however, no difference was found at the ultra-distal radius. Conclusion Women 19-43 years of age using either one of these two contraceptive implants for 36 months had lower BMD values at the distal radius compared to pre-insertion values; however, no difference was found at the ultra-distal radius.